2018
DOI: 10.1186/s12245-018-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of pediatric patients presenting at Cambodian referral hospitals without appointments: an observational study

Abstract: BackgroundEmergency medicine is a young specialty in many low- and middle-income countries (LMICs). Although many patients seeking emergency or acute care are children, little information is available about the needs and current treatment of this group in LMICs. In this observational study, we sought to describe characteristics, chief complaints, management, and outcomes of children presenting for unscheduled visits to two Cambodian public hospitals.MethodsChildren enrolled in the study presented without appoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…222 49113 4433 (38) 40 49149 (42) Janajati 2546 (44) 1068 (47) 932 (42) 193 (43) 117 4644 5031 (38) 161 (46) Dalit 507 (9) 219 (10) 193 (9) 30 719 78 ( Presentation to ED, n (%)* 08:00-16:00 weekdays 1037 (24) 481 (28) 322 (19) 96 2837 2023 (38) 24 (40) 54 2216:00-08:00 or holidays 465 (27) 567 (34) 76 (22) 56 3019 3217 (28) 67 (27) ICU or OT or Referred 341 (8) 126 7117 726 826 1418 307 1221 ( Other complaints included musculoskeletal, neurology, urinary, cardiovascular diseases or complaints, psychology, and other general complaints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…222 49113 4433 (38) 40 49149 (42) Janajati 2546 (44) 1068 (47) 932 (42) 193 (43) 117 4644 5031 (38) 161 (46) Dalit 507 (9) 219 (10) 193 (9) 30 719 78 ( Presentation to ED, n (%)* 08:00-16:00 weekdays 1037 (24) 481 (28) 322 (19) 96 2837 2023 (38) 24 (40) 54 2216:00-08:00 or holidays 465 (27) 567 (34) 76 (22) 56 3019 3217 (28) 67 (27) ICU or OT or Referred 341 (8) 126 7117 726 826 1418 307 1221 ( Other complaints included musculoskeletal, neurology, urinary, cardiovascular diseases or complaints, psychology, and other general complaints.…”
Section: Resultsmentioning
confidence: 99%
“…Broadly, infections and injuries are dominating in unselected pediatric emergency patients, and typically children in these EDs are young with a median age 2 to 7 years in studies including children up to 13 or 18 years. 25 , 27 Interestingly, several pediatric studies reported that boys are considerably overrepresented: in Pakistan 60% were boys, 22 a study from Malaysia reported male to female ratio of 1.5:1, 24 a Cambodian study reported 54% boys, 27 and a large study from India reported a male to female ratio of 3:1. 23 It is noteworthy that recent report 28 from the COVID19 epidemic in China also indicates over representation of males among hospitalized cases that may indicate a sex-related susceptibility to serious infections, related to male sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…using written referral slips increases the likelihood a given referral will be successfully completed 11 , and can improve the accuracy and reduce redundancy of care provided by receiving practitioners. 34 , 35 The use of such communication tools is recommended by many expert groups and systems, including the WHO's Integrated Management of Childhood Illness program.…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%
“…Also, without a structured referral communication system, communication of critical patient information from referring providers to ambulance staff and receiving providers is sporadic, leading to gaps and delays in care. 11 With only a small number of facilities having adopted referral qualityimprovement and feedback measures, challenges are slow to be identified and addressed.…”
mentioning
confidence: 99%